Collaborative Governance in Eliminating Papua Separatist Movement - Roy Valiant Salomo, Stepi Anriani, Amy Yayuk Sri Rahayu (International Journal of Advanced Science and Technology, 2020)
Papua Separatist Movement has existed since 1961 in the form of armed, political and clandestine movement. The Government of Indonesia has made an optimum effort in eliminating this movement by establishing collaborations of inter-regional governments, central-regional governments and with international parties as well. The difficult situation faced until today is that such movement still creates problems for the government of Indonesia, and even it tends to threaten the nation’s disintegration. The purpose of this research is to discover a suitable format of Collaborative Governance that can be implemented to handle Papua Separatist Movement in Papua Province Indonesia.The methodology is built up based on the Post Positivist Paradigm, where deductively, the Ratner’s concept of Collaborative Governance and the criteria of success of Collaborative Governance of Goldsmith and Kettl are used to portrait the Collaborative Governance in eliminating Free Papua Movement in Papua.The result is that during the first phase, the distributive accountability indicator and information sharing did not run smoothly. During the second phase, the Governance indicator failed to be performed due to loss of trust among actors. During the third phase, almost all indicators in Ratner’s Theory have not yet been fulfilled.As a conclusion, in handling Papua Separatist Movement in Papua, the Ratner’s perspective needs to be developed further because there are many contextual variables that need to be taken into account in Collaborative Governance. A dialogue effort and establishment of suitable institutional design are required in eliminating this Papua case.